The taste enhancer divanillin: a review on sources and enzymatic generation. (12th May 2015) - Krings, Ulrich; Esparan, Vida; Berger, Ralf G.
Abstract Dehydrodivanillin, the symmetrical dimer of vanillin, is a taste enhancer which imparts pleasant impressions of creaminess to food. Found in vanilla pods in traces only, a co‐substrate independent dimerization of vanillin, conducted in a co‐solvent system to improve the solubility of vanillin, was developed using iso‐active fungal laccases from Meripilus giganteus, Agaricus bisporus and Funalia trogii. The yields were compared with a peroxidase from Marasmius scorodonius (MsP2) and the reference enzyme horseradish peroxidase (HRP), both supplied with hydrogen peroxide. Using laccase catalysis, the kinetically preferred reaction product, 5, 5'‐dehydrodivanillin, rapidly reached saturation and precipitated in situ, thus shifting the reaction equilibrium to the product. Yields of > 95 % were obtained with the high‐redox‐potential laccase of Funalia trogii, while HRP gave 18 %. Copyright © 2015 John Wiley & Sons, Ltd.